Application of Data Quality Management Platform in Inner Mongolia Power Company - Yu Zhang; Hongfang Pan (Dianxin kexue)
The data quality management platform was designed and constructed while the data center was building, which could help to realize scientific and effective data management and quality control. In addition, the trusted data could provide reliable decision support for decision makers. Based on these systems, it was further analyzed that how to build a set of quality management system from two aspects, such as information technology and management control. With the help of reliable data and quality analysis system, the quality of enterprise data was significantly improved, and the accurate scientific data was ensured to be provided by data center systems.